Fluorescence imaging as a diagnostic of M-band x-ray drive condition in hohlraum with fluorescent Si targets. (8th December 2016) - Li, Qi; Hu, Zhimin; Yao, Li; Huang, Chengwu; Yuan, Zheng; Zhao, Yang; Xiong, Gang; Qing, Bo; Lv, Min; Zhu, Tuo; Deng, Bo; Li, Jin; et al.
Abstract: Fluorescence imaging of surrogate Si-doped CH targets has been used to provide a measurement for drive condition of high-energy x-ray (i.e. M-band x-ray) drive symmetry upon the capsule in hohlraum on Shenguang-II laser facility. A series of experiments dedicated to the study of photo-pumping and fluorescence effect in Si-plasma are presented. To investigate the feasibility of fluorescence imaging in Si-plasma, an silicon plasma in Si-foil target is pre-formed at ground state by the soft x-ray from a half-hohlraum, which is then photo-pumped by the K-shell lines from a spatially distinct laser-produced Si-plasma. The resonant Si photon pump is used to improve the fluorescence signal and cause visible image in the Si-foil. Preliminary fluorescence imaging of Si-ball target is performed in both Si-doped and pure Au hohlraum. The usual capsule at the center of the hohlraum is replaced with a solid Si-doped CH-ball (Si-ball). Since the fluorescence is proportional to the photon pump upon the Si-plasma, high-energy x-ray drive symmetry is equal to the fluorescence distribution of the Si-ball.